Carotid Intima-Media Thickness Assessment in Children with Nephrotic Syndrome - Esfandiar, Nasrin; Mohkam, Masoumeh; Dalirani, Reza; Hosseini Tabatabaei, Seyed Mohammad Taghi; Khalili, Mitra; Hajipour, Mahmoud; Yavari, Maedeh; Jamily, Reyhaneh; Ahmadi, Samaneh (Novelty in Biomedicine, 2024)
Background: Carotid intima medial thickness (CIMT) is a reliable marker for assessing large and medium blood vessel atherosclerosis. This study aimed to investigate the carotid intima-media thickness in children with nephrotic syndrome admitted to Mofid Hospital during 2019-2021. Materials and Methods: This case-control study was conducted in Mofid Hospital for two years (2019-2021). The samples were selected in the case group from hospitalized children with nephrotic syndrome and the control group from hospitalized children without nephrotic syndrome. Results: The mean thickness of the right and left carotid intima-media thickness in the case group was 0.07 ± 0.43 and 0.43 ± 0.07 millimeters, respectively, and these two values were lower and equal to 0.42 ± 0.05 millimeters in the control group, respectively (P-value= 0.02, P-value = 0.016). There was a negative and significant relationship between the level of phosphate and CIMT on the left side, and with an increase of one unit in phosphate, the value of left CIMT decreased by 0.277 times. Also, there was a negative and significant relationship between right CIMT and the level of albumin at discharge time, so with an increase of one unit in albumin, the value of right CIMT decreased by 0.256 times. Conclusion: It is concluded that nephrotic syndrome causes an increase in CIMT and vascular damage in children. The increase of blood albumin and phosphate was associated with the decreased CIMT.